The Relationship Between Students' Perceptions of Physical Education Subjects and Their Motivation to Study Physical Education at Kartika XIX-2 Junior High School in Bandung - Windy Aulia Putri; Toto Subroto; Agus Gumilar (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study looks at how students view Physical Education, Sports, and Health classes and how that ties into their drive to learn at Junior High School Kartika XIX-2 in Bandung. The whole thing started because students often see these classes in a low light and lack real motivation for them. People still treat PE like its just an extra thing, not the main focus. Researchers went with a quantitative method and a correlational setup to dig into this. The group they studied included every student at that school. For the sample, they picked 105 students through simple random sampling. They gathered data using a questionnaire with closed questions on a 4-point Likert scale. To analyze it, they ran the Spearman's Rho correlation test since the data did not follow a normal distribution. The findings pointed to a very strong positive link between how students perceive PE and their motivation to learn, with an r value of 0.889 and p less than 0.05. That means the better students feel about PE, the more motivated they get to engage. These results really highlight why teachers need to step up and create positive views through fun, hands-on strategies that make sense and fit the Independent Curriculum principles.